“ÜÇ VAKTE KADAR”IN BEŞ BİN YILLIK EVRİMİ - Özen, Abdullah (Mersin University, 2013)
Sümerler, Akadlar, Babiller ve Asurlar başta olmak üzere, Eski Dünya olarak tanımlanan coğrafî alanda yaşamış olan insan topluluklarının birçoğu, hastalıkların prognozunun belirlenmesinde karaciğer falını kullanmışlardı. Hepatoskopi olarak adlandırılan bu fal türü, tanrıya ya da tanrılara kurban edilen koyunun karaciğerindeki şekillerin yorumlanması esasına dayanmaktaydı. İnanışa göre, koyun kutsal bir hayvandı. Koyunun karaciğeri ise yaşamın merkezi olduğu için gelecek bilgisi taşımaktaydı. İnsanlık tarihinin binlerce yıllık bölümünde kullanılmış olan bu teknik, biyoloji ve tıp alanındaki bilimsel gelişmelere bağlı olarak, yerini zamanla rasyonel uygulamalara bırakıp yok olmuştur. Ancak, insanoğlunun geleceği öğrenme merakı asla yok olmayacak gibi görünmektedir. Nitekim karaciğer falının türevi niteliğindeki falcılık uygulamalarının günümüzdeki yaşayan örneklerinin, bu iddiayı desteklediği düşünülebilir

The majority of the communities that have dwelled in the geographical region referred to as the Old World, like the Sumerians, Akkadians, Babylonians and Assyrians, used liver reading as a tool to determine disease prognosis. This type of fortune-telling, also referred to as hepatoscopy, was based on the reading of the figures in the liver of a sheep sacrificed for the god(s). The sheep was believed to be a sacred animal, while, on the other hand, the liver of the sheep, was believed to hold information of the future, as it was considered the core of life. This technique of fortune-telling, which was used for thousands of years throughout the history of mankind, was replaced by rational applications in the course of time and in parallel with scientific developments achieved in the fields of biology and medicine, and eventually disappeared.However, it appears that the curiosity of mankind in the future will never end. As a matter of fact, it is considered that today’s fortune-telling practices, which have derived from hepatoscopy, are in support of this claim
A FIVE-THOUSAND YEAR EVOLUTION OF FORTUNE-TELLING